The plants that feed the world: baseline data and metrics to inform strategies for the conservation and use of plant genetic resources for food and agriculture - Khoury, Colin K.; Sotelo, Steven Humberto; Hawtin, Geoffrey C.; Wibisono, Jasmine; Amariles, Daniel; Guarino, Luigi; Kiene, Tobias; Toledo, Alvaro (2022)
Information on the use of food and agricultural crops and on interdependence regarding, demand for, supply of, and security of their genetic resources is needed to prioritize conservation and utilization efforts. This information is increasingly available but is scattered through several information systems, databases and scientific literature. The study The plants that feed the world: Baseline data and metrics to inform strategies for the conservation and use of plant genetic resources for food and agriculture intends to bring together and make widely available pertinent information from these different sources. The aim is to develop a set of reproducible metrics that provide an evidence base for the international plant genetic resources community to prioritize conservation and utilization activities. Measured periodically, these metrics can also provide insights on change over time in the use of crops and issues regarding interdependence on, demand for, supply of, and security of their genetic resources.